Study of Serum Magnesium Levels in Patients Admitted with Sepsis in Intensive Care Unit - Patil, PSG; Aslam, SS (Kathmandu University Medical Journal, 2023)
Background Magnesium plays an important role in sepsis, and this could be attributed to its effects on the immune system, which are important in the pathogenesis of sepsis. Magnesium deficiency, one of the underrated electrolyte abnormalities, is observed in critically ill patients admitted to intensive care unit (ICU).Objective To find the association of serum magnesium with the outcome, duration, and need for ventilation.Method The hospital-based prospective observational study included patients > 18 years (N=150) with sepsis admitted to intensive care unit. Patients were divided into normomagnesemia (n=75) and hypomagnesemia (n=75) groups. Sequential Organ Failure Assessment Score (SOFA) score, length of intensive care unit stay, need and duration of mechanical ventilatory requirement, and outcomes were compared between the two groups.Result The mean Sequential Organ Failure Assessment score (5.87 ± 2.31 vs. 3.85 ± 1.75), mean duration of intensive care unit stay (in days) (7.21 ± 1.74 vs. 5.24 ± 1.38), the mean duration of mechanical ventilatory requirement (in days) (4.05 ± 3.47 vs. 1.13 ± 1.98), and mortality rate were (33% vs. 4%) were higher in the hypomagnesemia group when compared to the normomagnesemia group (p < 0.001 for all).Conclusion The study concludes that hypomagnesaemia is a significant electrolyte abnormality in critically ill sepsis patients. Hypomagnesaemia, Sequential Organ Failure Assessment Score, and mechanical ventilation are the factors that independently predicted mortality in intensive care unit patients. Hence, clinicians should regularly monitor the occurrence of hypomagnesemia in intensive care unit patients to reduce its poor clinical outcomes.